2022
DOI: 10.1515/mammalia-2021-0087
|View full text |Cite
|
Sign up to set email alerts
|

An unusually big challenge: first record of Leopardus guigna preying upon Pudu puda

Abstract: Notwithstanding the very small size of this felid, Leopardus guigna is considered a top predator within its habitat. Its diet consists of small mammals, birds and reptiles, according to the available literature, but its predatory behaviour has rarely been observed directly. Here we report the first record of L. guigna preying upon Pudu puda in southern Chile. Photographic material has been obtained in a citizen science project and indicates a significant expansion of the cat’s prey size range. It also adds val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Leopardus guigna was also seen resting on tree branches and stumps of fallen trees (Fig. 6; Sanderson et al 2002), and swimming on occasion (Kaiser et al 2022). Night resting sites consisted of thick piles of live or dead vegetation, often dense bamboo thickets (Sanderson et al 2002).…”
Section: Ecologymentioning
confidence: 98%
See 1 more Smart Citation
“…Leopardus guigna was also seen resting on tree branches and stumps of fallen trees (Fig. 6; Sanderson et al 2002), and swimming on occasion (Kaiser et al 2022). Night resting sites consisted of thick piles of live or dead vegetation, often dense bamboo thickets (Sanderson et al 2002).…”
Section: Ecologymentioning
confidence: 98%
“…Of those species known to be sympatric with L. guigna , the lesser grison ( Galictis cuja ), culpeo fox ( Lycalopex culpaeus ), nutria ( Myocastor coypus ), American mink ( Neogale vison ), and pudu ( Pudu pudu ) are considered too large to be prey of L. guigna . Any occurrence of these species in the diet is likely behavioral evidence of scavenging (Freer 2004; Correa and Roa 2005); however, one L. guigna was observed preying on a pudu indicating a significant expansion in prey size range (Kaiser and Guzmán Marín 2022). One occurrence of domestic sheep wool suggested that L. guigna stole mutton from a local market (Freer 2004).…”
Section: Ecologymentioning
confidence: 99%